Examining Techno-Stress and Work–Personal Conflict of Gig Workers in the Indian IT Sector : The Moderating Role of Gender - Kumari, K. Thriveni (Prabandhan: Indian Journal of Management, 2025)
Purpose : Gig workers in the IT industry are employed on a contract basis for a paid project, typically for a short period. The purpose of the study was to examine the techno-stress (TS) of gig workers working in the IT sector. Design/Methodology/Approach : The study was conducted with 294 gig workers working in various Indian IT companies. Further, the study examined the role of gender as a moderator. Using factor analysis, correlation, and hierarchical regression analysis, the data were analyzed and explained with SPSS 21.0. Interaction software was used to explain the moderating effect of gender. Findings : Technical ambiguity, technical burden, job risk (JR), technical complexities, and managerial support are the variables considered for reading the TS effect on personal-work conflict of gig workers. The results showed that all the variables considered for TS had a significant influence on the work–personal conflict of gig workers. Further, the study also identified variations in the case of gender as moderators, which resulted in a significant relationship between the variables. Therefore, the study addressed the need to consider the determinants that influenced TS among gig workers in the IT industry. Practical Implications : The article provided policies that would reduce the gig workers’ TS and improve the quality of work and personal life domains. Originality/Value : The article helped to understand how TS influenced work–personal conflict, which is identified to be useful for gig employees working in the IT sector.